Analisis Tingkat Kepuasan Nasabah Dan Bentuk Promosi Terhadap Program Tabungan Pada Bank ABC - Danial Kesa, Deni (Research and Community Service UNIVERSITAS KALBIS, 2024)
The Indonesian banking sector has undergone swift expansion propelled by technology innovations. Companies confront competition by enhancing customer pleasure with diverse offerings customized to meet consumer requirements, hence insuring customer retention. This study seeks to examine the influence of customer satisfaction (X) on the Savings Program (Y) at PT Bank ABC. The study population comprises both existing and potential clients of PT Bank ABC. The study utilizes a descriptive quantitative methodology, employing questionnaires as the principal instrument for data collection. The analytical approach employs multiple linear regression, facilitated by SPSS Statistics 25 software. The outcomes of multiple assessments demonstrate that customer satisfaction has a positive and substantial impact on the Savings Program and the techniques employed by the organization.